ANALISIS KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA (PERIODE 2016-2019) - Rati Wulandari (2020)
This study aims to determine the firm's characteristics on firm value. The firm's characteristics consist of a capital structure proxied by Debt to Equity Ratio (DER), firm size proxied by Ln Total Asset (SIZE), liquidity Proxied by Current Ratio (CR), and profitability proxied by Return on Equity (ROE) on firm value indicated by Price to Book Value (PBV). The population in this study are the industrial sector of consumer goods listed on the Indonesia Stock Exchange (IDX) period of 2016-2019.The sampling techniques used in this stud were purposive sampling and acquired 27 industrial sectors of consumer goods with a four-year research period to acquire 108 sample units. Data analysis are using Microsoft Excel 2013 and hypothesis test in this study using the Data regression analysis Panel with the E-Views 10.0 program and a signification rate of 5%. The results of this study shows that the (1) Capital structure has a positive and significant effect on the firm value, (2) Firm size has no significant effect on the firm value, (3) Liquidity has no significant effect on the firm value, (4) Profitability has no significant effect on the firm value.